The trophoblast giant cells of cricetid rodents - Favaron, Phelipe O.; Carter, Anthony M. (Frontiers in Cell and Developmental Biology, 2023)
Giant cells are a prominent feature of placentation in cricetid rodents. Once thought to be maternal in origin, they are now known to be trophoblast giant cells (TGCs). The large size of cricetid TGCs and their nuclei reflects a high degree of polyploidy. While some TGCs are found at fixed locations, others migrate throughout the placenta and deep into the uterus where they sometimes survive post partum. Herein, we review the distribution of TGCs in the placenta of cricetids, including our own data from the New World subfamily Sigmodontinae, and attempt a comparison between the TGCs of cricetid and murid rodents. In both families, parietal TGCs are found in the parietal yolk sac and as a layer between the junctional zone and decidua. In cricetids alone, large numbers of TGCs, likely from the same lineage, accumulate at the edge of the placental disk. Common to murids and cricetids is a haemotrichorial placental barrier where the maternal-facing layer consists of cytotrophoblasts. These are characterized as sinusoidal TGCs. The maternal channels of the labyrinth are supplied by trophoblast-lined canals. Whereas in the mouse these are lined largely by canal TGCs, in cricetids canal TGCs are interspersed with syncytiotrophoblast. Transformation of the uterine spiral arteries occurs in both murids and cricetids and spiral artery TGCs line segments of the arteries that have lost their endothelium and smooth muscle. Since polyploidization of TGCs can amplify selective genomic regions required for specific functions, we argue that the TGCs of cricetids deserve further study and suggest avenues for future research.